A Fourier perspective in multi-legged systems - Rodrigues, Carlos M. B. (2001)
This paper analyses periodic gaits of multi-legged locomotion systems. The joint signals are studied in the Fourier domain, namely from the point of view of its reproducibility through low-pass actuators. The influence of several parametrs is also considered and their critical values are investigated.